Impact of vaginal distention on cell senescence in an animal model of pelvic organ prolapse. (December 2021) - Hare, Adam M.; Gaddam, Neha G.; Shi, Haolin; Acevedo, Jesus F.; Word, R. Ann; Florian-Rodriguez, Maria E.
Highlights: This is the first study examining the role of cellular senescence in the development of pelvic organ prolapse. Vaginal distention downregulates p53 and γ-H2Ax in wild-type mice. Fibulin-5 knockout mice, predisposed to pelvic organ prolapse, are not protected from cellular senescence. Abstract: Objective: Cellular senescence, associated with aging, leads to impaired tissue regeneration. We hypothesize that vaginal injury initiates cell senescence, further propagated during aging resulting in pelvic organ prolapse (POP). Our objective was to employ a mouse model of POP (Fibulin-5 knockout mice, Fbln5 -/- ) to determine if vaginal distention leads to cellular senescence and POP. Methods: 6wk old females [wild-type (WT), n = 81; Fbln5 -/-, n = 47)] were assigned to control vs vaginal distention, which approximated vaginal delivery. Serial POP measurements were obtained until vagina were harvested from euthanized mice at 24, 48, 72 h and 1wk. Markers of cell senescence were quantified by immunofluorescence. DNA damage was assessed with γ-H2Ax . Results: WT distended mice showed decreased p53 (p = 0.0230) and γ-H2Ax (p = 0.0008) in vaginal stromal cells at 1wk compared to controls. In WT mice, SA-β-Gal activity increased 1wk after distention (p = 0.05). In Fbln5 -/- mice, p53 and γ-H2Ax did not decrease, but p16 decreased 72 h after distention (p = 0.0150). SA-β-Gal activity also increased in Fbln5 -/-, but at earlier time points and 1wk after distention (p < 0.0001). Fbln5 -/- mice developed POP after distention earlier than non distended animals (p = 0.0135). Conclusions: Vaginal distention downregulates p53 and γ-H2Ax in WT mice, thereby promoting cell proliferation 1wk after injury. This was absent among Fbln5 -/- distention mice suggesting they do not escape senescence. These findings indicate a failure of cellular protection from senescence in animals predisposed to POP.